2008
DOI: 10.1007/s10535-008-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of alternative oxidase chain under salt stress conditions

Abstract: This paper describes the effect of NaCl on the respiration of Citrus cell suspensions namely on the induction of the alternative oxidase. The exposure of two Citrus (cvs. Carvalhal tangor and Valencia late) cell suspensions to 200 or 400 mM NaCl lead to a reduction on cell respiration rates. Under these conditions, the respiration rate decreased less in the presence of KCN indicating a stimulation of the capacity of the alternative oxidase (AOX). In addition, immunoblots showed an increase on the amount of AOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…H 2 O 2 -pretreated plants had a better ability to scavenge superoxide radical. Regulation of the synthesis of alternative oxidase (AOX) was also crucial in the tolerance of plants to salt stress (Ferreira et al 2008). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 -pretreated plants had a better ability to scavenge superoxide radical. Regulation of the synthesis of alternative oxidase (AOX) was also crucial in the tolerance of plants to salt stress (Ferreira et al 2008). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work reported that treatment with high concentrations of NaCl leads to an increase in cyanide-resistant respiration and AOX expression in plant calli or cell suspension cultures (Ferreira et al, 2008;Wang et al, 2010). However, there is a remarkable lack of knowledge about the responses of AOX to salt stress in plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work reported that treatment of Citrus cell suspensions with high concentration of NaCl led to a stimulation of the capacity of the AOX pathway and an increase in AOX protein amount (Ferreira et al 2008). However, the response of the AOX pathway to salt stress, especially at the whole-plant level, is not fully understood.…”
Section: Introductionmentioning
confidence: 99%